2022
DOI: 10.1371/journal.pone.0276603
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic characterization of endolysins and holin-like membrane proteins in the lysis cassette of phages that infect Gordonia rubripertincta

Abstract: Holins are bacteriophage-encoded transmembrane proteins that function to control the timing of bacterial lysis event, assist with the destabilization of the membrane proton motive force and in some models, generate large “pores” in the cell membrane to allow the exit of the phage-encoded endolysin so they can access the peptidoglycan components of the cell wall. The lysis mechanism has been rigorously evaluated through biochemical and genetic studies in very few phages, and the results indicate that phages uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 74 publications
(173 reference statements)
0
8
0
Order By: Relevance
“…The high level of toxicity following the expression of these proteins is especially intriguing given the low sequence conservation of the three proteins: although Girr gp35 and Waterfoul gp32 are members of the same pham, they only share 35% amino acid identity, and Hammy gp32 is part of a separate pham with only ∼20% identity to the other two proteins. Although the single TMD proteins are not annotated as holins, a recent report on >80 actinobacteriophages that infect Gordonia rubripertincta ( Pollenz et al . 2022 ) shows that the lysis cassette may contain up to four different holin-like genes where the terminal gene typically encodes a protein with a single TMD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high level of toxicity following the expression of these proteins is especially intriguing given the low sequence conservation of the three proteins: although Girr gp35 and Waterfoul gp32 are members of the same pham, they only share 35% amino acid identity, and Hammy gp32 is part of a separate pham with only ∼20% identity to the other two proteins. Although the single TMD proteins are not annotated as holins, a recent report on >80 actinobacteriophages that infect Gordonia rubripertincta ( Pollenz et al . 2022 ) shows that the lysis cassette may contain up to four different holin-like genes where the terminal gene typically encodes a protein with a single TMD.…”
Section: Resultsmentioning
confidence: 99%
“…2022 ), and TOPCONS ( Tsirigos et al 2015 ). TMD proteins were characterized based on agreement of all three programs as detailed in Pollenz et al . (2022) .…”
Section: Methodsmentioning
confidence: 99%
“…The holin gene encodes for a protein of size 7.4 kDa, which shares 61.1% identity with the holin from cluster I2 mycobacteriophage Che9c. Comparable to other phage-encoded holin, this, too, consists of two transmembrane helices, which could destabilize the membrane proton motive force of the host in a time-dependent manner (Pollenz et al, 2022). phiE1336 demonstrates distinct PGBD and EAD.…”
Section: The Lytic Cassette In Prophage Phie1336mentioning
confidence: 99%
“…Soos shares 84.1% GCS with annotated phage Clawz (GenBank accession MT498058) , and 90.6% GCS with the draft genome of phage Sting ( https://phagesdb.org/phages/Sting ), the only other phages in cluster CP. Like Clawz, Soos includes a simple lysis cassette with a single, large endolysin gene preceding a holin gene ( 16 ). Nucleotide sequence comparison of Soos using BLASTn revealed that outside of cluster CP, Soos is most similar to GMA4 (GenBank accession NC_030939.1 ), a phage without sufficient GCS to be assigned to any cluster and with which Soos shares ~4% GCS.…”
Section: Announcementmentioning
confidence: 99%